Curcumin Conjugated with PLGA Potentiates Sustainability, Anti-Proliferative Activity and Apoptosis in Human Colon Carcinoma Cells - Waghela, Bhargav N. (PLoS One, 2015)
Curcumin, an ingredient of turmeric, exhibits a variety of biological activities such as anti-inflammatory, anti-atherosclerotic, anti-proliferative, anti-oxidant, anti-cancer and anti-metastatic. It is a highly pleiotropic molecule that inhibits cell proliferation and induces apoptosis in cancer cells. Despite its imperative biological activities, chemical instability, photo-instability and poor bioavailability limits its utilization as an effective therapeutic agent. Therefore, enhancing the bioavailability of curcumin may improve its therapeutic index for clinical setting. In the present study, we have conjugated curcumin with a biodegradable polymer Poly (D, L-lactic-co-glycolic acid) and evaluated its apoptotic potential in human colon carcinoma cells (HCT 116). The results show that curcumin-PLGA conjugate efficiently inhibits cell proliferation and cell survival in human colon carcinoma cells as compared to native curcumin. Additionally, curcumin conjugated with PLGA shows improved cellular uptake and exhibits controlled release at physiological pH as compared to native curcumin. The curcumin-PLGA conjugate efficiently activates the cascade of caspases and promotes intrinsic apoptotic signaling. Thus, the results suggest that conjugation potentiates the sustainability, anti-proliferative and apoptotic activity of curcumin. This approach could be a promising strategy to improve the therapeutic index of cancer therapy.